Pengaruh Citra Merek dan Kualitas Pelayanan Terhadap Kepercayaan Warga di Yayasan Al-Sakinah Jakarta - Alda Naidiya; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
This study was conducted to determine the effect of brand image and service quality on citizen trust in the Al-Sakinah Foundation Jakarta. In this study, the method used is Probability Sampling with a sample size of 109 respondents by distributing questionnaires that are distributed via google form. Data analysis was performed using SPSS version 25. Based on the results of the t test partially, the brand image variable (x1) has a significant and significant effect on the citizen trust variable and the service quality variable shows that the service quality variable has an effect on and is significant to the citizen trust variable. In addition, the results of this study with the F test, with results 145.432 > table f 3.082 shows that simultaneously the variables of brand image and service quality have an effect on citizen trust.